2003
DOI: 10.1557/proc-772-m4.7
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly Fabrication of High Performance Carbon Nanotubes Based FETs

Abstract: We describe the realization of high quality self-assembled single wall carbon nanotube field effect transistors (CNTFET). A method using self-assembled monolayers (SAMs) is used to obtain high yield selective deposition placement of single wall carbon nanotubes (SWNTs) on predefined regions of a substrate. This is achieved with individual or small bundles of SWNTs and with high densities suitable for fabrication of integrated devices. We show that such positioned SWNTs can be electrically contacted to realize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The SWNTs are then connected in a transistor geometry (Cr/Au source and drain electrodes, spaced by 100 to 500 nm) using the heavily doped and oxidized silicon substrate (200 nm of SiO 2 ) as back-gate. Elaborating on pioneering works using an electrostatic interaction between the SWNTs and the SAM, we recently showed that a high yield of highly selective deposition of individual SWNTs in predefined areas of the substrate, and thus a high yield of CNTFETs fabrication, was possible using simultaneously a SWNT organic solvent dispersion and deposition on an optimized SAM. The SWNT raw material used in the present work was produced by a laser ablation technique at Dresden University and purified by an optimized soft acidic treatment . The purified SWNTs were dispersed by moderate sonication in N -methyl pyrrolidone (NMP), which proves the solvent of choice for a high yield of selective deposition onto the APTS patterns.…”
mentioning
confidence: 99%
“…The SWNTs are then connected in a transistor geometry (Cr/Au source and drain electrodes, spaced by 100 to 500 nm) using the heavily doped and oxidized silicon substrate (200 nm of SiO 2 ) as back-gate. Elaborating on pioneering works using an electrostatic interaction between the SWNTs and the SAM, we recently showed that a high yield of highly selective deposition of individual SWNTs in predefined areas of the substrate, and thus a high yield of CNTFETs fabrication, was possible using simultaneously a SWNT organic solvent dispersion and deposition on an optimized SAM. The SWNT raw material used in the present work was produced by a laser ablation technique at Dresden University and purified by an optimized soft acidic treatment . The purified SWNTs were dispersed by moderate sonication in N -methyl pyrrolidone (NMP), which proves the solvent of choice for a high yield of selective deposition onto the APTS patterns.…”
mentioning
confidence: 99%
“…This approach has the potential to generate functional multicomponent devices by self-assembly of the atoms and molecules without wasting them or the need for eliminating parts of the system [17]. The assembly of the elementary building blocks is usually manipulated by either physical aggregation, chemical reaction, or use of templates [3,24] where controlled chemical reactions manipulate the building blocks to self-assemble and make nanostructures such as nanotubes, nanoribbons, and quantum dots [1,25,26]. This approach has the potential to assemble nanostructured materials where the top-down approach fails though one of its major challenges is to ensure predefined structures with precise shapes and sizes [3].…”
Section: Fabrication Of Nanostructured Materialsmentioning
confidence: 99%
“…Choi et al [90] patterned a PMMA mask with e-beam lithography, and a deposited amino-silane SAM and subsequent surfactant-covered CNTs were patterned by lift-off. Valentin et al [91] present CNT-based field-effect transistors using similar self-assembly methods followed by metal lithography.…”
Section: A Self-assembled Monolayers (Sams) For Antistiction Wear Rmentioning
confidence: 99%